The weight of networks: the role of social ties and ethnic media in mitigating obesity and hypertension among Latinas. Issue 7 (3rd October 2019) - Walter, Nathan; Robbins, Chris; Murphy, Sheila T.; Ball-Rokeach, Sandra J.
ABSTRACT: Objectives: Latinos have a disproportionately high risk for obesity and hypertension. The current study analyzes survey data from Latin American women to detect differences in rates of obesity and hypertension based on their number of health-related social ties. Additionally, it proposes individuals' health-related media preference (ethnic/ mainstream) as a potential moderator. Design: The dataset includes 364 Latinas (21–50 years old) from the greater Los Angeles metropolitan area, who responded to a series of sociodemographic, physiological, health-related, and media-related questions. Results: Controlling for various sociodemographic and health variables, each additional health-related tie in a Latina's social network significantly decreased her likelihood of being obese OR = .79, p = .041, 95% CI [.66, .95], but did not affect hypertension. Further, the analysis revealed a significant interaction between media preference and health-related social ties, such that exposure to ethnic media tended to compensate for the absence of social ties for the likelihood of obesity OR = .75, p = .041, 95% CI [.52, .97], as well as hypertension OR = .79, p = .045, 95% CI [.55, .98]. Conclusion: In concurrence with the literature, increases in health-related ties reduced the likelihood of obesity in this population. Moreover, ethnic media preference may play an important role in mitigating the likelihood of obesity and hypertension among Latinas.